Influence of the Linker Chemistry on the Photoinduced Charge-Transfer Dynamics of Hetero-dinuclear Photocatalysts - Zedler, Linda; Müller, Carolin; Wintergerst, Pascal; Mengele, Alexander K.; Rau, Sven; Dietzek-Ivanšić, Benjamin (Chemistry - A European Journal, 2022)
To optimize light-driven catalytic processes, light-mediated multi-electron transfer dynamics in molecular dyads need to be studied and correlated with structural changes focusing on the catalytically active metastable intermediates. Here, spectro-electrochemistry has been employed to investigate the structure-dependent photoelectron transfer kinetics in catalytically active intermediates of two Ru−Rh catalysts for light-driven NAD+ reduction. The excited-state reactivity of short-lived intermediates was studied along different photoreaction pathways by resonance Raman and time-resolved transient absorption spectro-electrochemistry with sub-picosecond time resolution under operando conditions. The results demonstrate, for the first time, how the bridging ligand serves as a (multi-)electron storage structure, mediates the strength of the electronic coupling of catalytic and photocenter and impacts the targeted electron transfer as well as parasitic electron-transfer kinetics.
CRIS-Team Scopus Importer:2023-11-13
Keywords: photocatalysis; resonance Raman spectroscopy; spectro-electrochemistry; transient absorption; ultrafast spectroscopy